Hubungan Antara Pola Asuh Orangtua, Teman Sebaya, Lingkungan Tempat Tinggal dan Sosial Ekonomi Dengan Kesehatan Mental Remaja : The Relationship Between Parenting Patterns of Parents, Peers, Living Environment and Socio-Economic With Adolescent Mental Health - Farah Nauroh Haniyah; Astrid Novita; Syarifah Nur Ruliani (Open Access Jakarta Journal of Health Sciences, 2022)
Introduction: Adolescence is a dynamic phase of development and undergoes many changes, these changes include physical, mental, social, and emotional changes. It is estimated that 10-20% of adolescents globally have mental health conditions, but these are still underdiagnosed and treated. In Indonesia, it is known that the estimated number of people with mental disorders worldwide is around 450 million, including schizophrenia (WHO, 2017). With Disability Adjusted Life Years (DALYs) is 4.5% and the cause of disability (YLDs) is greater than other diseases, namely 13.4%. Riskesdas (2018) results show that depressive disorders have started to occur since the adolescent age range (15-24 years), with a prevalence of 6.2%. The available data shows that there are not a few people with mental health disorders in adolescents. Factors that influence mental health problems in adolescents are the family environment, peers, school environment, community environment and social media. The family environment referred to here is parenting style, uncomfortable place to live, and lower socioeconomic status of parents. Objective: This study aims to determine the relationship between parenting patterns and adolescent mental health, the relationship between peers and adolescent mental health, the relationship between living environment and adolescent mental health, and the relationship between socioeconomic status and adolescent mental health. Methods: This type of research uses a quantitative approach with a descriptive type. The design of this study used a cross-sectional study method. The sampling technique used is the Non Probability Sampling technique, namely Purposive Sampling. The sample used was 121 students of SMKN 62 South Jakarta. The instruments used are the Self Reporting Questionnaire (SRQ) the and Parental Authority Questionnaire (PAQ). Used as 121 students at SMKN 62 South Jakarta. Results: The p-value between parenting and adolescent mental health is 0,029 < 0,05. The results of the p-value of peers with adolescent mental health are 0,006 < 0,05. The result of the p-value between the neighborhood and the mental health of adolescents is 0,042 < 0,05. And the results of the p-value between the socio-economic and mental health of adolescents are 0,044 <0,05. Conclusion: Of all the variables (parental parenting, peers, living environment, and socio-economic) that exist, the results show that all variables have a relationship with adolescent mental health.